Direct survival role of vascular endothelial growth factor (VEGF) on rat ovarian follicular cells - Irusta, Griselda (2010)
The aim of the present work was to analyze the direct effect of VEGF in follicular cell proliferation, apoptosis and activation of the PI3K/AKT and ERK/MEK signaling pathways in early antral follicles or granulosa cells. Antral follicles or granulosa cells were isolated from prepubertal female Sprague Dawley rats treated with DES.VEGF directly stimulates follicular cell proliferation and it also decreases apoptosis by inhibiting caspase 3 activation. In addition, VEGF increases the proliferation and inhibits the apoptosis of isolated granulosa cells in culture. VEGF activates the PI3K/AKT pathway evidenced by an increase in AKT phosphorylation levels and induces the phosphorylation of ERK1/2 in cultured antral follicles. These results demonstrate for the first time that VEGF has a proliferative and cytoprotective role in early antral follicles and in granulosa cells isolated from DES treated prepubertal rats and suggest that PI3K/AKT and ERK/MEK signaling pathways are involved in these processes.